Large scale industrial enterprises in Turkish industry: their structures, characteristics and spatial distribution - Temurçin, Kadir (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
Industrialization is a process which is based on precise and quantitative measurements andcontains different basic changes in the economic structure of a country or region. The structural characteristicsand spatial distribution of the industrial enterprises established during the industrialization processwhich is one of the most important elements of the socio-economic transformation in Turkey withina historical process has been the object of this study. The aim of the study was to establish the positionsand significance of one thousand (1000) large industrial companies in the industry of Turkey by usingthe framework of criteria based on sales from production which have been maintained by the IstanbulChamber of Industry on a regular basis. The workplace and number of employees of the companies ona province basis, sector based division, realized exports and sales from product output, corporate entities,structures, spatial distribution and other characteristics were taken into consideration in the study.Although the thousand large scale companies in Turkey based on production output sales comprised only0.40% of the enterprises active in the industrial sector in 2012, they comprised 12% of the labor force,59.6% of product output sales and 65.2% of all exports. On a regional basis, 54% of these companiesare located in the Marmara region, 13.2% are located in Central Anatolia and 12.4% are located in theAegean region; on a province basis, 63.4% are located in Istanbul, Izmir, Bursa, Kocaeli and Ankara.A sector based division of the companies shows that 21.4% are involved in food, beverage and tobaccoprocessing, 19.6% are involved in the industry of metal goods, machinery, automotive industry, electricaltools and equipment and 16.1% deal with textiles, ready-to-wear, leather and the manufacturingof shoes. In terms of labor force numbers, the figures vary as 18.9%, 27.4% and 17.9% respectively.